Badiiy matndagi bilim tuzilmalarining metaforik representatsiyasi - Tumparova, Guzal (The Lingua Spectrum, 2025)
The article examines the problem of metaphorical representation of knowledge structures in literary texts. It is noted that metaphoricality is a characteristic of literary texts, which are marked by allegory and imagery. The tendency of literary speech towards metaphoricality is due to the author’s departure from the ordinary view and "thinking" in images. At the same time, the author’s metaphor is the foundation for creating an "authorial world." It is emphasized that the most promising approach to studying metaphor is the cognitive-stylistic approach. This approach allows for the synthesis of the tools and possibilities of stylistics and cognitive linguistics, exploring the interaction between language and thought, and facilitating interdisciplinarity (combining knowledge from various fields such as linguistics, psychology, philosophy, and literary studies). Attention is drawn to the fact that metaphor plays a key role in representing knowledge structures, allowing for the transmission of both old and new information, activating various areas of knowledge. Based on the analysis of examples from English-language literary texts, it is concluded that metaphors activate universal and culturally specific representations of reality through the prism of images and concepts characteristic of different cultures.